2020
DOI: 10.21203/rs.3.rs-17276/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of aging on the biological and immunological characteristics of periodontal ligament stem cells

Abstract: Abstract Background: Periodontal ligament stem cells (PDLSCs) have many applications in the field of cytotherapy, tissue engineering, and regenerative medicine. However, the effect of age on the biological and immunological characteristics of PDLSCs remains unclear. Methods: In this study, we compared PDLSCs isolated from young and adult individuals. PDLSCs proliferation was analyzed by Cell Counting Kit-8 (CCK-8) and 5-ethy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…FKBP1A is recognized as autophagy‐related gene, which is a target of drugs including Rapamycin and FK506 (Feng et al, 2021; Ghartey‐Kwansah et al, 2018; Liu et al, 2017). Some studies found that FKBP1A is involved in aging, apoptosis, and proliferation (Leng et al, 2020; Li et al, 2020; Seguinot‐Tarafa et al, 2020). Besides, FKBP1A is implicated in inflammation by complementary DNA (cDNA) array results and genomic network results (Saban et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…FKBP1A is recognized as autophagy‐related gene, which is a target of drugs including Rapamycin and FK506 (Feng et al, 2021; Ghartey‐Kwansah et al, 2018; Liu et al, 2017). Some studies found that FKBP1A is involved in aging, apoptosis, and proliferation (Leng et al, 2020; Li et al, 2020; Seguinot‐Tarafa et al, 2020). Besides, FKBP1A is implicated in inflammation by complementary DNA (cDNA) array results and genomic network results (Saban et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The specific method of Western blot was described in our previous study. 26 Primary antibodies used include JNK (1:1000; CST), P-JNK (1:1000;…”
Section: Western Blot Analysismentioning
confidence: 99%
“…A functional shortage in adult stem cells caused by cellular senescence may be regarded as a major driver of age-related deterioration in endogenous tissue healing and regenerative potential (Sharpless and DePinho 2007). Li et al (2020) illustrated the effects of age on periodontal ligament stem cells (PDLSCs) by comparing PDLSCs from young and elderly donors. They found that the proliferation, osteogenic/adipogenic/chondrogenic differentiation, and immunosuppressive ability of PDLSCs decreased, whereas apoptosis increased with the aging process.…”
Section: Molecular Hallmarks Of Aging In Periodontal Tissuesmentioning
confidence: 99%